The School Environmental Factors that affect the Academic Performance of Senior High Financial Accounting Students in Tamale Metropolis in the Northern Region of Ghana - Joseph, Osei Tutu (Advances in Social Sciences Research Journal, 2014)
The purpose of this paper was to examine the school environmental factors that affect the academic performance of Senior High financial accounting students in the Tamale Metropolis of Ghana. Twenty nine (29) teachers and two hundred and sixty (260) financial accounting students from the seven (7) senior high schools in the municipality were selected for the study. It was a descriptive study where questionnaire was used to collect the data. The study revealed that availability of residential facilities in schools and instructional materials have a positive influence on the level of students’ academic performance in financial accounting. Students who have access to relevant instructional materials such as recommended text books, ICT and library facilities use those materials to supplement their learning endeavours. The study also recommended that, government should put policy framework and structures in place in order to provide residential facilities to most day schools, if not all, and provide those schools with the necessary residential facilities.